Differential Pattern of cAMP Response Element-Binding Protein Activation in the Rat Brain after Conditioned Aversion as a Function of the Associative Process Engaged: Taste versus Context Association - Desmedt, Aline (J Neurosci, 2003)
Ample data indicate that cAMP-response element-binding protein (CREB) is essential for the formation of long-term memory in various species and learning systems. This implies that activated CREB could delineate neuronal circuits that subserve items in memory, while leaving open the possibility that the specifics of CREB activation itself contribute to the specificity of the internal representation encoded by the relevant circuit. We describe here the differential activation of CREB in the rat brain as a function of two related yet distinct forms of aversive conditioning: conditioned taste aversion (CTA) and conditioned context aversion (CCA). We found that CTA induces strong CREB activation in the insular cortex (IC) and the lateral septum (LS), but not in the parietal cortex (PC) and the medial septum (MS). In contrast, CCA results in strong activation in the PC and MS, but not in the IC and LS. These findings are congruent with a model that links differential pattern of activity within the LS and the MS with the acquisition of elemental versus contextual conditioning and, more generally, with the notion that CREB activation delineates learning-dependent circuits as a function of the type of cognitive process engaged.